Linking State-Owned Enterprises And Energy Diplomacy - Muhammad Rum; Bangkit Aditya Wiryawan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Natural resources endowment has always been a critical factor in supporting a country’s development, particularly in its early stage, where firm productivity in industry and service sectors are still low. Such is the case with Indonesia, one of the largest oil-producing countries in the East Asia region, where the oil boom period in the 1970s has been able to fund many development projects. Although oil resources have been waning over the last decade, the country is still among the largest producers in the Southeast Asian region, with an also growing demand for the burgeoning industry. The problems are doubled by a high demand for energy from Indonesia’s domestic market which has worsened trade deficit in recent years. State-owned enterprises have been mandated by the government to perform better in securing energy deals. Hence, this study aims to survey on what kind of role state-owned enterprises can partake in to strengthen Indonesia’s energy diplomacy. The scope of study encompasses energy policies of selected countries since the Oil Shock until recent developments today. This work is utilizing a comparative study of examples from other influential oil-seeking countries such as Japan and China, recent improvement in some developing countries that includes renewable energy sector. We also evaluate ‘petrodollar’ diplomatic strategies such as Venezuela and Saudi Arabia. It is argued that state-owned enterprises should actively engage in promoting development in targeted countries and maintaining bilateral ties. Furthermore, this article proposes an approach of what could be done by scholars to help in formulating Indonesia’s energy diplomacy. The conclusion of this study indicates strong correlations between energy security, international diplomacy, and development assistance. Balancing those nexuses will help Indonesia in exercising its free and active diplomatic stance in resolving various international issues. The promotion of norms and values can serve a potential role in boosting Indonesia’s energy diplomacy.